(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2002)
Some issues related to the obsessive-compulsive diagnosis have been analyzed by behavior therapists mainly through the avoidance/escapement concepts. Basically the treatment proposed involves exposition to unleashed stimuli of anxiety and/or obsessions. This work assumes that response patterns involved in this kind of problem comprehend other contingences besides the avoidance/escapement of anxiety stimuli. Under this perspective, several events from the environment that could support the installation and maintenance of the problem are pondered, including situations such as social reinforcement, task escapements, and privation and aversive stimulation conditions. From the analysis of these feasible contingences, some alternative proposals to the standard procedures applicable to the obsessive-compulsive behavior are presented, mainly embracing the alteration of contingences in the natural environment and in the therapeutic relationship.